Lomitapide affects HDL composition and function. (August 2016) - Yahya, R.; Favari, E.; Calabresi, L.; Verhoeven, A.J.M.; Zimetti, F.; Adorni, M.P.; Gomaraschi, M.; Averna, M.; Cefalù, A.B.; Bernini, F.; Sijbrands, E.J.G.; Mulder, M.T.; et al.
Abstract: Background: Lomitapide reduces low-density lipoprotein-cholesterol (LDL-C) but also high-density lipoprotein-cholesterol (HDL-C) levels. The latter may reduce the clinical efficacy of lomitapide. We investigated the effect of lomitapide on HDL-C levels and on cholesterol efflux capacity (CEC) of HDL in patients with homozygous familial hypercholesterolemia (HoFH). Methods and results: Four HoFH patients were treated with increasing dosages of lomitapide. Lomitapide decreased LDL-C (range −34 to −89%). Total HDL-C levels decreased (range −16 to −34%) with a shift to buoyant HDL. ABCA1-mediated CEC decreased in all patients (range −39 to −99%). The changes of total, ABCG1- and SR-BI-mediated CEC were less consistent. Conclusion: Lomitapide decreased LDL-C and HDL-C levels. Our report raises the hypothesis that the anti-atherogenic potential of HDL seems to be unaffected as total CEC did not seem to change consistently. Combined with the reduction of atherogenic lipoproteins, the net effect of lomitapide appears to be beneficial in HoFH patients. Graphical abstract: Highlights: Lomitapide decreases HDL-C in HoFH patients, while the cholesterol efflux capacity of HDL does not change consistently. Lomitapide treatment of HoFH patients leads to a shift of HDL to more buoyant particles. Lomitapide leads to a shift in cholesterol efflux pathways, to a relatively lower contribution of the ABCA1 pathway.